Anticytokine autoantibodies in infection and inflammation: an update. Issue 6 (December 2016) - Barcenas-Morales, Gabriela; Jandus, Peter; Döffinger, Rainer
Abstract : Purpose of review: Concise overview of the field of anticytokine autoantibodies with a focus on recent developments. Recent findings: Advances in particular in the analysis of autoantibodies to IFNγ, granulocyte-macrophage colony-stimulating factor (GM-CSF) and type I IFN are presented. The target epitope for anti-IFNγ autoantibodies has been found to have high homology to a protein from Aspergillus suggesting molecular mimicry as a mechanism of breaking self-tolerance. A treatment strategy using a recombinant, epitope-depleted version of IFNγ is suggested. Autoantibodies to GM-CSF are associated with disseminated Crytococcus and Nocardia infections thus expanding the spectrum of associated diseases beyond pulmonary alveolar proteinosis. Detailed analysis of anti-GM-CSF autoantibody clones derived from pulmonary alveolar proteinosis patients show evidence of high somatic mutation suggesting T cell-dependent affinity maturation; full GM-CSF neutralization is achieved by synergistic binding of antibodies targeting various distinct noncross-reactive epitopes and leading to antigen sequestration and Fc-mediated clearance. Single mAbs in contrast may lead to higher GM-CSF bioavailability. Anti type I IFN-specific autoantibodies derived from autoimmune polyglandular syndrome type I patients are of extreme high affinity and negatively correlate with the incidence of type I diabetes and may be thus considered to be protective. Hypomorphic severe combined immune deficiency may be associated with complex anticytokine patterns and the emergence of anti type I IFN autoantibodies correlates with severe viral infection histories. Summary: Anticytokine autoantibodies may cause susceptibility to infections. In autoimmune/autoinflammatory conditions, anticytokine autoantibodies may be protective or promote disease.